Laboratory-scale photomineralization of n-alkanes in gaseous phase by photocatalytic membranes immobilizing titanium dioxide - Ignazio Renato Bellobono; Rodica Stanescu; Cristina Costache; Carmen Canevali; Franca Morazzoni; Roberto Scotti; Riccardo Bianchi; Emilia Simona Mangone; Giulia de Martini; Paola Maria Tozzi (International Journal of Photoenergy)
Kinetics of photocatalytic oxidation of methane, ethane, and n-heptane, to yield intermediates, and photomineralization of intermediates, to yield carbon dioxide and water, was studied in the gaseous phase, at 308±2 K, by a laboratory-scale photoreactor and photocatalytic membranes immobilizing 30±3 wt.% of TiO2, in the presence of aerosolized stoichiometric hydrogen peroxide as oxygen donor, and at a relative humidity close to 100%. The whole volume of irradiated solution was 4.000±0.005 L, the ratio between this volume and the geometrical apparent surface of the irradiated side of the photocatalytic membrane was 3.8±0.1 cm, and the absorbed power was 0.30 W/cm (cylindrical geometry). The pinetic parameters of the present work substantially coincide with those of the same molecules previously studied in aqueous solution, within the limits of experimental uncertainty. Photocatalytic processes thus appear to be controlled by interface phenomena, which are ruled kinetically, and apparently also thermodynamically, by concentration gradients, independently on diffusion and other processes in the aqueous or gaseous bulk, if turbulence in these phases is adequately assured.